Measuring dimensions of service quality - Tešić Dejan (Strategic Management, 2020)
In the modern business environment, service companies face the challenge of continuous improvement of the quality of services. Retail managers must use an adequate system for evaluating the quality of the services they provide within the retail establishment. One of the tools that managers use is SERVQUAL analysis, which consists of five dimensions in the traditional model. The aim of this paper is to highlight the importance and necessity of measuring the dimensions of service quality in retail outlets. The subject of this paper is investigating the attitudes of customers in a retail store in Bosnia and Herzegovina, on the perception and expectations of the quality of services provided to them. The results of the study indicate that the gap between performance and expectations of all dimensions is negative, i.e. that none of the performance according to the dimensions of the SERVQUAL model exceeded respondents' expectations.